Nothing about us without us : disability oppression and empowerment - Charlton, James I. (University of California Press, 1998)
James Charlton has produced a ringing indictment of disability oppression, which, he says, is rooted in degradation, dependency, and powerlessness and is experienced in some form by five hundred million persons throughout the world who have physical, sensory, cognitive, or developmental disabilities. Nothing About Us Without Us is the first book in the literature on disability to provide a theoretical overview of disability oppression that shows its similarities to, and differences from, racism, sexism, and colonialism. Charlton's analysis is illuminated by interviews he conducted over a ten-y.